The Use of Information Technology in Territorial Planning of a Subject of the Russian Federation - Sheina, S G; Chubarova, K V; Girya, L V; Seferyan, L A (IOP conference series. Materials Science and Engineering, 2020)
To date, the most important task in the modern Russian cities' development is the formation and maintenance of an environment favorable and comfortable for the population. The authors of the article describe the main problems and directions of the construction industry and territorial planning modernization in the Russian Federation. The article details the national project "Housing and Urban Environment", its goals and objectives, analyzes one of the project's priority areas - the state program "Formation of a Comfortable Urban Environment", developed for the period from 2018 to 2024. A drawback of the existing methodology for assessing the urban environment quality in terms of assessing the environmental situation is noted. An example of the alternative methodology implementation for calculating the habitat quality index for a site in the city of Rostov-on-Don, which takes into account the environmental pollution factors in more detail, is given.